Language Learners or New Speakers: The Transfer of the Breton Diwan Immersion Education Model to the Lower Sorbian Witaj Project - Dołowy-Rybińska, Nicole (Studia Celtica Posnaniensia, 2017)
The paper discusses several aspects of immersion and bilingual education systems in Brittany, France and in Lower Lusatia, Germany. Their role in the process of becoming a new speaker of a minority language is exemplified by the Diwan immersion education model in Brittany and the Witaj project in Lower Lusatia concerning the Sorbian people. Taking into consideration the different sociolinguistic situation of both groups, the level and reasons for language shift, the existing language policy in France and in Germany, both educational models are presented. I analyze some factors that influence the possible success or failure of these two models, such as: the linguistic environments, teaching systems, the roles of teachers, the minority language attitudes of pupils, their language practices, the availability of extracurricular activities in the minority language, and the existence of different types of communities of practice. All these factors influence pupils’ language choices and practices. Not all language learners will use a minority language in the future, since it depends on the conscious decision of each person. The distinction between language learners and minority language new speakers can thus be justified.